Plant Genomics 2009
DOI: 10.21775/9781912530069.04
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Phenotypes Reveal a Functional Expression of OsARF1 , an Auxin Response Factor, in Transgenic Rice

Abstract: The editor of this timely book has assembled a team of highly regarded scientists, over 40 contributors, to describe the latest, up-to-date research, theory and applications of this increasingly important area of science.Renowned experts in the field have contributed chapters that describe and discuss some of the most topical aspects of plant genomics. The book is fully illustrated and chapters include comprehensive reference sections.Essential reading for scientists involved in plant genomics and a recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 0 publications
1
58
0
Order By: Relevance
“…Recent studies showed that PIN1-mediated auxin transport was related to cellular differentiation during maize embryogenesis and endosperm development [46] and essential role of OsARF1 in rice seed development [47]. Altered auxin signaling in seeds may cause abnormal development, proposing an “autonomous” mechanism of auxin signaling in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that PIN1-mediated auxin transport was related to cellular differentiation during maize embryogenesis and endosperm development [46] and essential role of OsARF1 in rice seed development [47]. Altered auxin signaling in seeds may cause abnormal development, proposing an “autonomous” mechanism of auxin signaling in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Closely related AtARF genes appear to have somewhat redundant roles in Arabidopsis. In rice, an antisense mutation of the OsARF1 gene resulted in a phenotype exhibiting low vigor, stunted growth, curled leaves, and sterility, which suggests that OsARF1 is vital for vegetative and reproductive development (Attia et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Those three phytochromes are involved in regulating flowering time (Takano et al, 2005;Kiyota et al, 2012), while the other TFs function primarily in developmental processes or stress responses. For example, OsARF1 regulates root and shoot lengths (Attia et al, 2009); rice indoleacetic acid1 (OsIAA1) controls leaf angle and root lengths (Song et al, 2009); SLR1 modulates cell division and expansion (UeguchiTanaka et al, 2007); homeodomain transcription factor 1a (HOX1a) regulates elongation of the uppermost internode (Wen et al, 2011); an OsHOX4 mutation causes dwarfism (Dai et al, 2008); outcurved leaf1 (OUL1) regulates leaf rolling (Zou et al, 2011); OsWRKY78 controls cell elongation ; rice histone associated protein 3A (OsHAP3A) and OsHAP3B influence chloroplast development (Miyoshi et al, 2003); rice P-deficiency responsive transcription factor 1 (OsPTF1) and…”
Section: Discussion Go Enrichment Reveals Essential Biological Procesmentioning
confidence: 99%
“…In three cases (Os11g32110, Os02g05840, and Os02g50550), expression levels were higher only in certain organs ( Figure 5A). Mutations in Os11g32110 (auxin response factor 1 [OsARF1]) affected root and shoot lengths (Attia et al, 2009); expression of that gene was higher when compared with its counterpart, Os12g29520. Mutations in Os02g05840 (rice leaf inclination2) affected leaf angles through brassinosteroid signaling (Zhao et al, 2010).…”
Section: Evaluation Of Functional Dominancy For Phenomic Analysis Usimentioning
confidence: 99%